Features of Neural Network Formation and Their Functions in Primary Hippocampal Cultures in the Context of Chronic TrkB Receptor System Influence - Mishchenko, Tatiana A.; Mitroshina, Elena V.; Usenko, Alexandra V.; Voronova, Natalia V.; Astrakhanova, Tatiana A.; Shirokova, Olesya M.; Kastalskiy, Innokentiy A.; Vedunova, Maria V. (Frontiers in Physiology, 2019)
Discovering the mechanisms underlying homeostatic regulation in brain neural network formation and stability processes is one of the most urgent tasks in modern neuroscience. Brain-derived neurotrophic factor (BDNF) and the tropomyosin-related kinase B (TrkB) receptor system have long been considered the main regulators of neuronal survival and differentiation. The elucidation of methods for studying neural network activity makes investigating the complex mechanisms underlying neural network structure reorganization during development and detecting new mechanisms for neuronal activity remodeling possible. In this in vitro study, we investigated the effects of chronic BDNF (the main TrkB stimulator) and ANA-12 (a TrkB receptor system blocker) administration on the formation of neural-glial networks. The formation of spontaneous bioelectrical activity and functional neural structure depend on TrkB receptors, and blocking TrkB receptors inhibits full bioelectrical activity development. Cross-correlation analysis demonstrated the decisive role of TrkB in the formation and “strengths” of activity centers. Even though an appropriate ANA-12 concentration is nontoxic to nerve cells, numerous cells in culture medium containing this reagent do not exhibit metabolic activity and are not functionally involved in signal transmission processes. Electron microscopy studies revealed that chronically influencing the TrkB receptor system significantly alters synaptic and mitochondrial apparatus capture in cells, and functional analysis of mitochondrial activity confirmed these findings. Because knowledge of interactions between TrkB-mediated regulation and the mitochondrial state under normal conditions is rather limited, data on these relationships are particularly interesting and require further investigation. Thus, we assume that the molecular cascades mediated by TrkB actively participate in the formation of functionally complete brain neural networks.